Sorption of radionuclides to building materials and its removal using simple wash solutions. Issue 2 (June 2016) - Kaminski, Michael; Mertz, Carol; Ortega, Luis; Kivenas, Nadia
Abstract: Decontamination after a nuclear or radiological release requires a detailed understanding of the materials hosting the contamination, the chemistry of the radionuclide, and the chemical properties of the decontamination agent. Urban contamination via a number of radiological release scenarios may require simple decontamination methods that can be deployed for wide-area decontamination. This paper investigates a number of factors of importance for developing such decontamination methods, focusing on cesium. These factors include the influence on decontamination approaches from the cesium deposition conditions, the urban building material composition and, when washing with an ionic solution that is utilized for decontamination, the composition of the wash solutions. In summary, the sorption chemistry of cesium onto urban building materials and roadways has been studied to develop simple decontamination methods that can be deployed for wide-area decontamination efforts. To improve the understanding of the sorption of cesium onto common urban building materials and roadways the desorption of cesium deposited from solution and as a dry powder was tested. Using ammonium (NH4 + ) salt solutions, we tested the desorption of ionic cesium bound to individual components of concrete and coupons of several common building materials. While the tests on concrete aggregate suggest that a concentration >10 mM NH4 + does not improve the desorption of cesium, tests on concrete, asphalt, marble, limestone and granite monoliths showed improved decontamination factors when the NH4 + concentration increased from 0.1 to 0.5 M. We also found that cesium as dry particulate material could be removed quite effectively although the contamination became tenacious upon wetting the surface.